The effects of home confinement on physical activity level and mental status in professional football players during COVID-19 outbreak - Dönmez, G.; Özkan, Ö.; Menderes, Y.; Torgutalp, S. S.; Karaçoban, L.; Denerel, N.; Kudas, S. (The Physician and Sportsmedicine, 2022)
Objectives: The coronavirus outbreak caused significant changes in football around the world, such as the suspension of leagues and home isolation of players, etc. The main purpose of the present study was to assess the psychological impacts of lockdown and similar restrictions on professional football players during the coronavirus pandemic. Materials and methods: The players from 36 professional football teams (n = 977) among Turkish Super League and First League teams were invited to complete a questionnaire including the Center for Epidemiologic Studies Depression Scale (CES-D), Impact of Event Scale-Revised Scores (IES-R) and short form of International Physical Activity Questionnaire (IPAQ). Results: The online survey was completed by 237 players (24.3%). The mean number of self-quarantine day of participants was 26.9 ± 6.2 days. The median CES-D Scale and IES-R scores were 6.0 (min:0, max:42) and 23.0 (min:0, max:59), respectively. IPAQ scores of the players showed that four-fifths of the players still maintain high physical activity levels. There were negative, very weak and significant correlations between CES-D score and being married (r = -0.146, p = 0.024), as well as between CES- D score and IPAQ-Walking (r = -0.189, p = 0.004). A significant positive very weak correlation was observed between CES-D score and self-quarantine days (r = 0.148, p = 0.024). IPAQ-Walking was an independent predictor of CES-D. Conclusion: These findings support that maintaining regular physical activity and routinely exercising in a safe home environment is one of the most important strategies to ensure healthy mental state.